Pengambilan Keputusan Kepala Madrasah - Alfiatun Fitriani Ulfah; Achadi Budi Santosa (Jurnal Ilmiah Wahana Pendidikan, 2020)
The head of the madrasah is the highest leader in the madrasah who also acts as a manager to manage and decide whether or not each input can process and interact positively in learning. The purpose of this study was to determine the types of decisions used by the head of madrasah in making decisions. This study took the setting at Madrasah Tsanawiah Negeri 8 Kebumen, while the research method used a qualitative approach with random sampling. The results of this study are that the majority of innovation decisions in madrasah are included in the type of collective innovation decisions, although some are categorized as authority innovation decisions. The innovation decision does not take place immediately, but through a process of a series of activities with an indefinite period of time.